2022
DOI: 10.1136/jitc-2021-004345
|View full text |Cite
|
Sign up to set email alerts
|

Durable and dynamic hTERT immune responses following vaccination with the long-peptide cancer vaccine UV1: long-term follow-up of three phase I clinical trials

Abstract: BackgroundTherapeutic cancer vaccines represent a promising approach to improve clinical outcomes with immune checkpoint inhibition. UV1 is a second generation telomerase-targeting therapeutic cancer vaccine being investigated across multiple indications. Although telomerase is a near-universal tumor target, different treatment combinations applied across indications may affect the induced immune response. Three phase I/IIa clinical trials covering malignant melanoma, non-small cell lung cancer, and prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…These findings support the concept that the long UV1 vaccine peptides contain multiple epitopes eliciting a diverse T cell response in each patient, rather than single vaccine-specific clonotypes. This hypothesis is further supported by previously published data on diversity among immune responder HLA genotypes and the various HLA restrictions and epitope specificities of vaccine-specific T cell clones [ 29 ]. Nevertheless, we identified TCR clonotypes that were significantly enriched after in vitro stimulation and subsequently detected them in unstimulated PBMCs and tumor tissue.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…These findings support the concept that the long UV1 vaccine peptides contain multiple epitopes eliciting a diverse T cell response in each patient, rather than single vaccine-specific clonotypes. This hypothesis is further supported by previously published data on diversity among immune responder HLA genotypes and the various HLA restrictions and epitope specificities of vaccine-specific T cell clones [ 29 ]. Nevertheless, we identified TCR clonotypes that were significantly enriched after in vitro stimulation and subsequently detected them in unstimulated PBMCs and tumor tissue.…”
Section: Discussionsupporting
confidence: 74%
“…Therapeutic cancer vaccines aiming to mount anti-hTERT immune responses have been evaluated with several platforms, including peptide, mRNA, and DNA-based approaches [ 28 ]. UV1 is a multipeptide therapeutic vaccine that has demonstrated HLA-independent induction of vaccine-specific T cell responses in patients treated across three completed phase I/IIa clinical trials [ 29 ]. Effective induction of robust T cell responses is a prerequisite for the potential clinical activity of a TCV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies on hTERT-based immunotherapy (three phase I/IIa clinical trials covering malignant melanoma, non-small-cell lung cancer, and prostate cancer) showed that UV1, a second-generation telomerase-targeting therapeutic cancer vaccine, triggered highly dynamic and persistent telomerase-peptide-specific immune responses that lasted up to 7.5 years after the initial vaccination. The superior immune response kinetics were observed in the melanoma study [ 97 ].…”
Section: Therapeutic Potential Of Telomerase Subunitsmentioning
confidence: 99%